Early and late complications arising from autologous soft tissue augmentation in dental practice: systematic review - M. Sheibanian; Z. S. Khabadze; Yu. A. Bakaev; N. N. Fedotova; M. M. Borlakova (LLC "Endo Press", 2022)
Aim. To consider and analyze early and late complications that occur during autologous soft tissue augmentation in dental practice, since knowledge of complications helps the doctor to choose the right approach and materials for the treatment of any disease.Materials and methods. The publications in the electronic databases PubMed , Google Scholar and other reliable resources, were studied during a systematic review of the literature. the author has selected articles whose content concerns the study of complications arising from autologous soft tissue augmentation in outpatient dental practice.Results. 71 articles we reviewed during the review. After analyzing the literature for inclusion criteria, the total number of publications has become 30.Conclusions. according to the studied literature, it can be assumed that the main complications arising from autologous soft tissue augmentation in dental practice include: bleeding, pain, swelling, increased sensitization, damage to nerve and/or vascular elements and flap necrosis.